Analysis of the Effectiveness of Using E-Commerce Marketplaces Shopee and Tokopedia in Loxus Living Company - Junaedi, Fajri; Salsabil, Sani; Ekawati, Risma; Faizah, Safira (Jakarta Global University, 2023)
The analysis reveals the impact of utilizing E-Commerce Marketplaces such as Shopee and Tokopedia in the strategies of Loxus Living Company.The adoption of e-commerce platforms like Shopee and Tokopedia plays a vital role for businesses aiming to enhance their competitiveness and sales in the modern digital landscape. This study delves into how Loxus Living Company leverages these marketplaces to boost its online visibility, drive sales, and monitor advancement towards set objectives. Factors such as user experience, safety, and transaction efficiency are considered when evaluating e-commerce success. The results illuminate how utilizing technology, and new media can boost business growth and expand the market.